Hubungan Self Disclosure dengan Komunikasi Interpersonal Mahasiswa Tingkat II Prodi Ners STIKES Santa Elisabeth Medan - Pomarida Simbolon; Rotua Elvina Pakpahan; Elvi Miranda Gultom (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
The purpose of this study was to determine the relationship between self disclosure and interpersonal communication of second degree students of STIKes Santa Elisabeth Medan in 2021. This research method used an analytical research design using a cross sectional approach. The sample in this study 86 respondents with the sampling technique is total sampling. The instruments used were a questionnaire, a standard self-disclosure questionnaire adopted from the sixty item self disclosure questionnaire (JSDQ) by Sidney M. Jourard and Paul Lasakow (1958) modified by previous researchers Tokan (2013) and an interpersonal communication questionnaire. The results of this study obtained self disclosure categories of high 55 people (64%) and low 31 people (36%), good categories of interpersonal communication 57 people (66.3%) and less 29 people (33.7%) with the Chi square test results obtained value The p-value of 0.001 (p<0.05) indicates that there is a relationship between self disclosure and interpersonal communication of second level students of the STIKes Santa Elisabeth Medan Nurse Study Program in 2021 which means that the higher the student's self-disclosure, the better the interpersonal communication will be. Open manner to telling attitudes and opinions, tastes and interests, work or studies, money, personality, and body will increase students' self-disclosure.